Pengaruh Social Media Marketing, Brand Image, dan E-WOM terhadap Keputusan Pembelian Produk The Body Shop - Amadhea Faustine Alvitasari; Donant Alananto Iskandar (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to explore the impact of social media marketing, brand image, and E-WOM on consumer purchasing decisions for The Body Shop products in Bekasi City. The methodology applied is a quantitative approach with a descriptive and causal research design. Data was collected through a questionnaire distributed to 180 respondents residing in Bekasi City who had purchased The Body Shop products and followed the brand's official social media accounts. Data analysis was conducted using IBM SPSS 27 statistical software, including validity and reliability tests, as well as tests of classical assumptions. The results indicate that all independent variables collectively have a significant influence on consumer purchasing decisions, with brand image being the most influential factor. The R² value of 0.543 indicates that 54.3% of the variation in purchasing decisions can be explained by this model, while the remainder is influenced by other variables not examined in this study.